Stretchable Loudspeaker using Liquid Metal Microchannel - Jin, Sang Woo; Park, Jeongwon; Hong, Soo Yeong; Park, Heun; Jeong, Yu Ra; Park, Junhong; Lee, Sang-Soo; Ha, Jeong Sook (NATURE PUBLISHING GROUP, 2015)
Considering the various applications of wearable and bio-implantable devices, it is desirable to realize stretchable acoustic devices for body-attached applications such as sensing biological signals, hearing aids, and notification of information via sound. In this study, we demonstrate the facile fabrication of a Stretchable Acoustic Device (SAD) using liquid metal coil of Galinstan where the SAD is operated by the electromagnetic interaction between the liquid metal coil and a Neodymium (Nd) magnet. To fabricate a liquid metal coil, Galinstan was injected into a micro-patterned elastomer channel. This fabricated SAD was operated simultaneously as a loudspeaker and a microphone. Measurements of the frequency response confirmed that the SAD was mechanically stable under both 50% uniaxial and 30% biaxial strains. Furthermore, 2000 repetitive applications of a 50% uniaxial strain did not induce any noticeable degradation of the sound pressure. Both voice and the beeping sound of an alarm clock were successfully recorded and played back through our SAD while it was attached to the wrist under repeated deformation. These results demonstrate the high potential of the fabricated SAD using Galinstan voice coil in various research fields including stretchable, wearable, and bio-implantable acoustic devices.
Keywords: HUMAN HEARING; DEVICES; ELECTRONICS; CONDUCTORS; GRAPHENE; TRANSPARENT; THERAPY; SENSOR; NANOGENERATOR; ACTUATOR